Staff Incentives Based on Kpi Principles - Zulunov Ravshanbek; Xadjayev Saidakbar (Periodica Journal, 2023)
Key performance indicators (KPI) - performance indicators of a unit (enterprise) that help the organization achieve strategic and tactical (operational) goals. The use of key performance indicators gives an organization an opportunity to assess its condition and help in assessing the implementation of the strategy
Keywords: Promotion; Proper Orientation; Eatability